No Difference in Postoperative Complications between Simultaneous and Staged, Bilateral Unicompartmental Knee Arthroplasty - Forlenza, Enrico M.; Serino III, Joseph; Shinn, Daniel; Gerlinger, Tad L.; Valle, Craig J. Della; Nam, Denis (The Journal of Knee Surgery, 2024)
The optimal timing of contralateral surgery following unicompartmental knee arthroplasty (UKA) remains unknown. Therefore, the objective of this study was to examine the differences in postoperative complications in patients undergoing unilateral, simultaneous, and staged bilateral UKA.The PearlDiver administrative claims database was queried for patients undergoing UKA between 2015 and 2020. Patients undergoing unilateral UKA were matched in a 1:1 fashion with patients undergoing simultaneous bilateral UKA, staged bilateral UKA within 1 to 90 days, and staged bilateral UKA within 91 to 365 days based on age, gender, Elixhauser Comorbidity Index (ECI), obesity, diabetes, and smoking status. Univariate and multivariate analyses were performed to examine the impact of timing of bilateral procedures on 90-day postoperative complications relative to patients who underwent unilateral UKA. Outcomes were considered significant at p < 0.05.A total of 9,638 patients undergoing UKA were included in the final analysis, of which 5,672 (58.9%) were unilateral, 396 (4.1%) were simultaneous bilateral, 1,496 (15.5%) were staged bilateral between 1 and 90 days, and 2,074 (21.5%) were staged bilateral between 91 and 365 days. Univariate analysis identified no significant differences in complications between matched groups except for an increased incidence of wound dehiscence among patients who underwent simultaneous bilateral UKA (2.1% vs. 0.0%, p = 0.040) compared with unilateral UKA. However, multivariate analysis demonstrated that simultaneous or staged bilateral UKA at either time point did not increase the risk of any postoperative complication relative to unilateral surgery.Bilateral UKA can be performed either simultaneous or in a staged fashion without increasing the risk of 90-day complications relative to unilateral UKA.
Keywords: knee arthroplasty; unicompartmental knee arthroplasty; postoperative complications